A alternância tu/você em contextos sintáticos de complementação e de adjunção: estudo de cartas pessoais dos séculos XIX e XX - Iracema Aguiar da Cruz (2017)
Since the results of previous researches attest that the syntactic function of subject was the main input to grammaticalized nominal forms, such as você and a gente into the pronominal system of Brazilian Portuguese, this work carries an analysis of other syntactic environments by means of which the form você was also gradually inserted into this system. Based on formal writing recorded in missives belonging to authors from Minas Gerais, and produced between the 19th and 20th centuries, this work aims to describe the productivity of você as a legitimate 2nd person singular pronoun in contexts of complementation and adjunction to the verb and to the noun, adopting the concept of predicator or predicative word, as stated by Duarte & Brito (2006), Raposo (2013), Ilari et alii (2015), for whom the term predicate embodies all and any word that have arguments, empty-spaces or own valence. In what concerns the terms projected by verbal predicators, the structures from the accusative, dative and oblique cases will be examined. Regarding the nominal predicators, the relations of complement and adjunct will be observed, also in the light of the concept of predicator. By assuming the present tense as the starting point to the description of the historical course traced by você non-subject, it justifies the adoption of the Uniformitarianism Principle (LABOV, 1994), as well as the conduction of this work under the methodological support of historical sociolinguistics (cf. ROMAINE, [1982] 2009, LOBO, 2001; CONDE SILVESTRE, 2007; HERNÁNDEZ-CAMPOY & CONDE SILVESTRE, 2012). The results show a major use of innovative você in contexts of complementation, projected by verbal predicates, overall, in structures of verbal complementation in dative and oblique cases. In this analysis, it is confirmed the hypothesis of formal and semantic parallelism, exposing that the highest productivity of você in complementation contexts is related to the high productivity of 3rd person singular pronominal forms (se, o/a, lhe, seu/sua), or to você-subject in precedent contexts. The tendency is for você-subject to foster related forms of você in contexts of complementation, as was also observed by Vianna e Lopes (2012) and Omena (2003) analyzing the form a gente.